2014
DOI: 10.3945/jn.114.196527
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Bioavailability of the Calcium Salt of β-Hydroxy-β-Methylbutyrate Is Greater Than That of the Free Fatty Acid Form in Rats

Abstract: This study demonstrates the enhanced relative bioavailability of CaHMB compared with FAHMB. Further studies are warranted to understand the physiologic mechanisms contributing to the differences in systemic clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
1
13
2
1
Order By: Relevance
“…Although both forms of HMB are equally effective on muscle function and are equally retained by the body over a 24 h period, the use of HMB-FA allows for more predictive timing of intake of HMB in relation to the planned exercise, thus achieving better outcomes, as was recently confirmed by Wilson et al (27) . Our human data differ considerably from the recently published data in rodents (33) , which reported that Ca-HMB had better availability as measured by peak blood levels when compared with HMB-FA. In that study, the investigators compared Ca-HMB with HMB-FA administration both orally in a liquid suspension and by intravenous injection, (33) and showed that similar amounts of HMB given as either Ca-HMB or HMB-FA resulted in the Ca-HMB having greater peak blood HMB concentrations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although both forms of HMB are equally effective on muscle function and are equally retained by the body over a 24 h period, the use of HMB-FA allows for more predictive timing of intake of HMB in relation to the planned exercise, thus achieving better outcomes, as was recently confirmed by Wilson et al (27) . Our human data differ considerably from the recently published data in rodents (33) , which reported that Ca-HMB had better availability as measured by peak blood levels when compared with HMB-FA. In that study, the investigators compared Ca-HMB with HMB-FA administration both orally in a liquid suspension and by intravenous injection, (33) and showed that similar amounts of HMB given as either Ca-HMB or HMB-FA resulted in the Ca-HMB having greater peak blood HMB concentrations.…”
Section: Discussioncontrasting
confidence: 99%
“…There are several concerns with comparison with the rodent study; the most notable is the concern related to species differences. For example, the half-life of HMB in blood after Ca-HMB dosing is reported as approximately 1, 2 and 3 h for the rat, pig and sheep, respectively (33)(34)(35) , compared with humans, with a half-life of 2•4 to 3•2 h for a 1 g dosage of Ca-HMB (14,15) . Other concerns relate to the experimental design, and the analytical methods used, as well as methodological differences related to the accuracy of HMB intake.…”
Section: Discussionmentioning
confidence: 99%
“…Fuller et al showed that administration of the free form of HMB resulted in more rapid and higher plasma concentrations and improved clearance of the HMB when compared with the calcium salt form and suggested that administration of HMB as free acid could improve HMB availability and efficacy to tissues 115. However, another study demonstrated higher bioavailability of HMB after administration of the calcium salt of HMB when compared with free‐acid form 116. Further studies are needed to determine the pros and cons of these two forms of HMB.…”
Section: Dosage and Drug Formsmentioning
confidence: 99%
“…115 However, another study demonstrated higher bioavailability of HMB after administration of the calcium salt of HMB when compared with free-acid form. 116 Further studies are needed to determine the pros and cons of these two forms of HMB.…”
Section: Healthy Subjects and Effects Of Hmb Consumptionmentioning
confidence: 99%
“…O principal destino metabólico do HMB parece ser a sua conversão para HMG-CoA a partir da desidratação para beta-metil-crotonil-CoA (MC-CoA) ou direta carboxilação para HMG-CoA em alguns tecidos, onde servem como fonte de carbonos para a síntese de colesterol. Cerca de 10% a 40% do HMB são excretados na urina (Nissen et al, 1997;Shreeram et al, 2014). Postula-se que o HMG-CoA citosólico produzido por HMB poderia ser fornecido como substrato para a enzima HMG-CoA redutase, que está relacionada a uma etapa importante na síntese de colesterol, que é necessário para a manutenção da integridade da célula, porém ainda não se sabe ao certo qual a porcentagem do carbono do colesterol deriva do HMB, e também como esta via afeta a síntese e degradação proteica Nissen et al, 1997;Vukovich et al, 2001b).…”
Section: Absorção De Hmbunclassified